2023
DOI: 10.1098/rspb.2022.2000
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of age-specific resistance to infectious disease

Abstract: Innate, infection-preventing resistance often varies between host life stages. Juveniles are more resistant than adults in some species, whereas the opposite pattern is true in others. This variation cannot always be explained by prior exposure or physiological constraints and so it has been hypothesized that trade-offs with other life-history traits may be involved. However, little is known about how trade-offs between various life-history traits and resistance at different life stages affect the evolution of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 68 publications
0
10
0
Order By: Relevance
“…Recent theory has shown how trade-offs and life-history traits combine to shape the evolution of age-specific resistance (Ashby and Bruns 2018 ; Buckingham et al 2023 ). Here, we have shown how the average age at which hosts become resistant evolves, depending on how and when costs of resistance are paid (costs only paid before or after the onset of resistance, or throughout the host’s lifetime).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent theory has shown how trade-offs and life-history traits combine to shape the evolution of age-specific resistance (Ashby and Bruns 2018 ; Buckingham et al 2023 ). Here, we have shown how the average age at which hosts become resistant evolves, depending on how and when costs of resistance are paid (costs only paid before or after the onset of resistance, or throughout the host’s lifetime).…”
Section: Discussionmentioning
confidence: 99%
“…The life stage at which trade-offs occur has a significant effect on the evolution of the rate of onset of resistance. It is well established that the magnitude and shape of trade-offs, as well as the life-history traits involved, are critical to the evolution of various traits, including resistance (Kisdi 2006 ; Ashby and Bruns 2018 ; Buckingham et al 2023 ). We have shown that the life stage at which trade-offs act also drastically alters the evolutionary outcome for the rate of onset of resistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent theory has shown how trade-offs and life-history traits combine to shape the evolution of age-specific resistance (Ashby and Bruns 2018; Buckingham et al 2023). Here, we have shown how the average age at which hosts become resistant (1/ ζ ) evolves, depending on how and when costs of resistance are paid (costs only paid before or after the onset of resistance, or throughout the host’s lifetime).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the evolution of age-structured resistance has received relatively little attention. However, recent theory has explored the evolution of age-specific resistance in juveniles and adults, showing that differences in resistance between life-stages are most pronounced for particularly long- or short-lived hosts (Ashby and Bruns 2018) and that adult resistance often evolves to exceed juvenile resistance, depending on which traits trade off with resistance (Buckingham et al 2023). Here, we investigate a different characteristic of age-specific resistance, namely the timing of the onset of resistance.…”
Section: Introductionmentioning
confidence: 99%